Purchasing planning for pharmaceuticals inventory: a case study of drug warehouse in hospital - Praphan Yawara; Naratip Supattananon; Pinpicha Siwapornrak; Raknoi Akarrungruangkul (Institute of Advanced Engineering and Science, 2023)
Lack of purchasing planning and proper demand forecasting causes hospitals to suffer from drug inventory mismatches with actual demand; in other words, the inventory management cost is high if the quantity exceeds or less the demand. Therefore, this research aimed to plan an appropriate inventory purchase to reduce inventory costs and effectively meet the hospital's pharmaceutical inventory needs in a case study: i) demand forecasting for 29 AV drugs using Minitab 19, ii) economic order quantity (EOQ) and Newsboy form when drug demand is stable and non-steady, respectively, and iii) design a ready-made program using Excel program to help control, make purchase decisions and be easy to use. There were 5 forecasting methods used. Each drug forecasting method was selected from the one with the slightest error. Twenty-four drugs and five drugs were determined using EOQ and Newsboy forms for re-order point (ROP), safety stock (SS), and total costs. The total cost of drug inventory management per year was 1,780,336.98 baht; compared with the current method, it reduced the cost by 506,569.10 baht per year or a 22.15% reduction.